Development of an Economic and Mathematical Model, Analysis and Transformation of the Hops Market in the Russian Federation in the Medium Term - Maria L. TOLSTOVA; Alexandra E. KORNILOVA (Communications of International Proceedings, 2025)
The article examines the state of hop production in the Russian Federation in connection with state regulation of the agricultural sector. Based on retrospective data and production factors, a mathematical and economic model of hop production development for the medium term is constructed. It is shown that within the framework of the model, at least a twofold increase in hop production is expected in the next 5 years with a high degree of reliability. Factors contributing to sustainable growth are analyzed and mechanisms for its intensification are given.
Keywords: hop growing; mathematical model; regression; timeseries analysis; gross production.